RANCANG BANGUN APLIKASI MONITORING PERILAKU DAN PERKEMBANGAN ANAK USIA DINI BERBASIS WEB DAN API - Oky Mikael; Nasrul Firdaus; Linda Suvi Rahmawati (Dinamika Dotcom : Jurnal Pengembangan Manajemen Informatika dan Komputer, 2025)
IQRO Kindergarten is an early childhood education institution that previously used a manual, book-based report card system. This system had several weaknesses, including the inability of parents to monitor their children's daily activities in real time, and teachers found it difficult to compile periodic reports for parents and school administrators.This research aims to develop a monitoring application using the SDLC method with a waterfall approach. This application is designed to provide teachers with flexibility in reporting student progress. In addition to numerical assessments, parents can now monitor their children's activities through photos and videos, thus maintaining transparency in school activities. The result of this research is a monitoring application that makes it easier for educators to systematically document children's development. This system also serves as an efficient reporting tool for teachers and a practical monitoring tool for parents and school administration.